2021
DOI: 10.11158/saa.26.4.11
|View full text |Cite
|
Sign up to set email alerts
|

<p class="Body"><strong>Functional response of <em>Amblyseius andersoni </em>and <em>Neoseiulus neoreticuloides</em> (Acari: Phytoseiidae) to adults of the wolfberry gall mite <em>Aceria pallida </em>(Acari: Eriophyoidae)</strong></p>

Abstract: The gall mite, Aceria pallida Keifer (Acari: Eriophyoidae) is an economically important pest of wolfberry Lycium barbarum L. and can cause significant losses to plant production. Two species of phytoseiid predatory mites, Amblyseius andersoni Chant and Neoseiulus neoreticuloides Liang & Hu were found on L. barbarum in Bayan Nur city, Inner Mongolia, China. We assessed the potential of these two phytoseiid species as biological control agents against A. pallida, using functional response experiments with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Effects of prey species on predator developmental duration are common in predatory mites and insects (Walzer et al 2004). In fact, C. lactis can serve as food for many predator mites, including Amblyseius andersoni (Chant) (Acari: Phytoseiidae) and Neoseiulus neoreticuloides (Liang et Hu) (Acari: Phytoseiidae) (Li et al, 2019;Fu et al, 2021). We found that N. barkeri could complete its growth and development on both C. lactis and M. usitatus, but it did so more rapidly when fed first instars of M. usitatus.…”
Section: Discussionmentioning
confidence: 77%
“…Effects of prey species on predator developmental duration are common in predatory mites and insects (Walzer et al 2004). In fact, C. lactis can serve as food for many predator mites, including Amblyseius andersoni (Chant) (Acari: Phytoseiidae) and Neoseiulus neoreticuloides (Liang et Hu) (Acari: Phytoseiidae) (Li et al, 2019;Fu et al, 2021). We found that N. barkeri could complete its growth and development on both C. lactis and M. usitatus, but it did so more rapidly when fed first instars of M. usitatus.…”
Section: Discussionmentioning
confidence: 77%
“…Effects of prey species on predator developmental duration are common in predatory mites and insects 47 . In fact, C. lactis can serve as food for many predator mites, including Amblyseius andersoni (Chant) (Acari: Phytoseiidae) and Neoseiulus neoreticuloides (Liang et Hu) (Acari: Phytoseiidae) 15 , 48 . We found that N. barkeri could complete its growth and development on both C. lactis and M. usitatus , but it did so more rapidly when fed first instars of M. usitatus .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Yao et al (2014), the predation of three predatory mites, N. cucumeris, N. barkeri, and E. nicholsi, was investigated, and it was found that all three species exhibited a type II functional response when preying on T. flavidulus. Phytoseiid species, Amblyseius andersoni (Chant) and Neoseiulus neoreticuloides (Liang & Hu), also exhibited a type II functional response to Aceria pallida Keifer (Eriophyidae) adults (Fu 2021). Similarly, Amblyseius cucumeris (Oudemans) (Phytoseiidae) was found to display a type II response when preying on F. occidentalis (Shipp and Whitfield 1991).…”
Section: Discussionmentioning
confidence: 99%